Quality management system to the agrobusiness of uchuva in the municipality of Ventaquemada - Gloria Acened Puentes Montañez, Nancy Cristina Sanabria Neira, (Universidad Pedagógica y Tecnológica de Colombia, 2011)
Colombia is a country still remains the primary economy (agriculture), and presents some shortcomings of an organizational nature, which means adopting strategies and basic development tools that come with the dynamics of the global market of food products, for the world agribusiness facing a radical change, requiring the application of technology and knowledge that allow to add value to their products due to the rapid growth of global trade in goods and services, innovation, customer pressure for quality goods The evolution of communication and competition. In this context, the agricultural sector should make efforts to modernize in order to meet the demands of customers worldwide, developing and improving their production and administrative processes for highly competitive products, respecting the environment and ensuring biotic conditions social justice for the actors, for it states the objective of implementing Quality Management Systems, which will allow production units to transform the traditional, modern companies and certified as a path to competitiveness, sustainability and equity of the sector.